PHOTODEGRADATION OF BATIK DYE COLOUR INDIGOSOL YELLOW IRK USING ZNO-CHITOSAN COMPOSITE - Hasri ummas; Eva Indriyani; Sitti Faika; Marlina Ummas Genisa; Haryanti Putri Rizal (Jurusan Kimia FMIPA Universitas Lampung, 2024)
This experiment research aims to determine the optimum conditions for degradation of Indigosol Yellow IRK batik dye using ZnO-Chitosan composite, including radiation time, dye concentration, pH and determining the effectiveness of degradation. Synthesis of ZnO-chitosan composite using wet impregnation method. Radiation time with variations in time of 10, 30, 60, 120, and 180 minutes, variation in dye concentration 50, 100, 150, 200, and 250 ppm, variation in pH of dye 2,5,7,9 and 11. Measurement of the resulting concentration dye degradation using a UV-Vis Spectrophotometer with a wavelength of 319 nm. A ZnO-chitosan composite was found to degrade Indigosol Yellow IRK batik dye at 180 minutes (98.28%), optimum concentration of 150 ppm (98.06%), optimum pH of 9 (98.98%). The photodegradation effectiveness test of the ZnO-chitosan composite using effective UV light was 5.60% compared to ZnO-chitosan without UV light. It was concluded that the ZnO-chitosan composite could degrade the Indigosol Yellow IRK batik dye so that the ZnO-chitosan-UV composite was more effectively used as an environmentally friendly dye degrader.